Desiminasi Kamus Praktis Bahasa Melayu Dialek Ternate untuk Wisatawan Lokal dan Internasional - Sulami Sibua; Erviani La Ane Mbongo; Widya Astuti Bilo; Mandaian Fitrianti M; Dewilsta Bunga; Alfandi Umaternate (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to identify word forms in Ternate Malay and Indonesian dialects and their structural meanings in Indonesian. And can be used as a communication guide for local and international tourists. This type of research uses descriptive qualitative research methods, the objects used in this research are: Malay dialect of Ternate. The data in this study are basic forms and word groups in Ternate Malay. While the data collection techniques used in the study were participant observation techniques, interviews, and documentation. The data analysis techniques in this study used qualitative data analysis techniques developed by Miles and Huberman, namely, starting with data reduction, data presentation, and withdrawal. conclusion. The results obtained in this study are in the form of word forms, such as personal pronouns, verbs, noun adjectives, adverbs from various fields accompanied by examples in the form of sentences. documentation. The data analysis technique in this study uses qualitative data analysis techniques developed by Miles and Huberman, namely, starting with data reduction, data presentation, and drawing conclusions. The results obtained in this study are in the form of words in the types of nouns, verbs, adjectives, and adverbs from various fields, such as economics, agriculture, fisheries, culture, politics, art, health, and other fields. practical dictionary of Ternate Malay dialect, which is useful for local and international tourists from various countries